Nantenna for Standard 1550 nm Optical Communication Systems - Waleed Tariq Sethi; Hamsakutty Vettikalladi; Habib Fathallah; Mohamed Himdi (International Journal of Antennas and Propagation)
Nanoscale transmission and reception technologies will play a vital role and be part of the next generation communication networks. This applies for all application fields including imaging, health, biosensing, civilian, and military communications. The detection of light frequency using nanooptical antennas may possibly become a good competitor to the semiconductor based photodetector because of the simplicity of integration, cost, and inherent capability to detect the phase and amplitude instead of power only. In this paper, authors propose simulated design of a hexagonal dielectric loaded nantenna (HDLN) and explore its potential benefits at the standard optical C-band (1550 nm). The proposed nantenna consists of “Ag-SiO2-Ag” structure, consisting of “Si” hexagonal dielectric with equal lengths fed by “Ag” nanostrip transmission line. The simulated nantenna achieves an impedance bandwidth of 3.7% (190.9 THz–198.1 THz) and a directivity of 8.6 dBi, at a center frequency of 193.5 THz, covering most of the ITU-T standard optical transmission window (C-band). The hexagonal dielectric nantenna produces HE20δ modes and the wave propagation is found to be end-fire. The efficiency of the nantenna is proven via numerical expressions, thus making the proposed design viable for nanonetwork communications.